(untitled) (Chemical Engineering Research Bulletin, 2017)
The aim of this paper is to discuss on the preservation of bioactive compound by using microencapsulation techniques. Microencapsulation is a process of building a functional barrier between the core and wall material to prevent any chemical or physical reactions. Microencapsulation provides an important technique in various food, pharmaceutical industry and textile product because has the ability to improve shelf-life, oxidative stability, provide protection and controlled biological activity release of active agents. Microencapsulation of plant extract, essential oils, vegetable has been developed and commercialized by employing various method including freeze drying, coacervation, spray drying, in situ polymerization and melt-extrusion. The most commonly used techniques for microencapsulation of oils are by using spray drying and coacervation method. Microencapsulation methods have been developed in order to modify the efficiency based on several factors such as types of active agents, shell material used, generating particles with a variable range of sizes, shell thickness and permeability. With this work, an overview regarding efficient and applications of microencapsulation process will be presented. Chemical Engineering Research Bulletin 19(2017) 50-56